Prognostic and Predictive Biomarkers in Patients With Coronavirus Disease 2019 Treated With Tocilizumab in a Randomized Controlled Trial*. Issue 3 (12th October 2021) - Tom, Jennifer; Bao, Min; Tsai, Larry; Qamra, Aditi; Summers, David; Carrasco-Triguero, Montserrat; McBride, Jacqueline; Rosenberger, Carrie M.; Lin, Celia J. F.; Stubbings, William; Blyth, Kevin G.; Carratalà, Jordi; et al.
Abstract : OBJECTIVES: To explore candidate prognostic and predictive biomarkers identified in retrospective observational studies (interleukin-6, C-reactive protein, lactate dehydrogenase, ferritin, lymphocytes, monocytes, neutrophils, d -dimer, and platelets) in patients with coronavirus disease 2019 pneumonia after treatment with tocilizumab, an anti–interleukin-6 receptor antibody, using data from the COVACTA trial in patients hospitalized with severe coronavirus disease 2019 pneumonia. DESIGN: Exploratory analysis from a multicenter, randomized, double-blind, placebo-controlled, phase 3 trial. SETTING: Hospitals in North America and Europe. PATIENTS: Adults hospitalized with severe coronavirus disease 2019 pneumonia receiving standard care. INTERVENTION: Randomly assigned 2:1 to IV tocilizumab 8 mg/kg or placebo. MEASUREMENTS AND MAIN RESULTS: Candidate biomarkers were measured in 295 patients in the tocilizumab arm and 142 patients in the placebo arm. Efficacy outcomes assessed were clinical status on a seven-category ordinal scale (1, discharge; 7, death), mortality, time to hospital discharge, and mechanical ventilation (if not receiving it at randomization) through day 28. Prognostic and predictive biomarkers were evaluated continuously with proportional odds, binomial or Fine-Gray models, and additional sensitivity analyses. Modeling in the placebo arm showed all candidate biomarkers except lactate dehydrogenase and d -dimer were strongly prognostic for day 28 clinical outcomes of mortality, mechanical ventilation, clinical status, and time to hospital discharge. Modeling in the tocilizumab arm showed a predictive value of ferritin for day 28 clinical outcomes of mortality (predictive interaction, p = 0.03), mechanical ventilation (predictive interaction, p = 0.01), and clinical status (predictive interaction, p = 0.02) compared with placebo. CONCLUSIONS: Multiple biomarkers prognostic for clinical outcomes were confirmed in COVACTA. Ferritin was identified as a predictive biomarker for the effects of tocilizumab in the COVACTA patient population; high ferritin levels were associated with better clinical outcomes for tocilizumab compared with placebo at day 28.